Internalization of Ethical Behavior Values in Local Language Lessons to Improve Student Politeness - Wilujengingati, Helmalia; Abidin, Muhammad Zainal; Putri, Yolanda Rahmadina; Ramli, M; Roida, Suwaslih; Saputra, Nur Mega Aris (Proceedings Series of Educational Studies, 2024)
This study aims to determine the influence of the internalization of ethical behavior values in local language lessons to improve student politeness. The progression of times has led to a decline in student politeness, necessitating teachers to take action to address this issue. One method employed by guidance and counseling teachers at SMK Muhammadiyah 1 Malang is incorporating ethical behavior values into local language lessons, particularly in the sections on etiquette and politeness. This study uses a qualitative descriptive method. Data collection techniques include interviews and observations. Interviews were conducted with five tenth-grade students. The results indicate that local language plays a significant role in enhancing politeness, as the subject contains several materials related to etiquette and politeness. Local language lessons accompanied by the internalization of ethical behavior values have helped students improve their politeness.